Monitoring Disease: Cause-of-Death-Registration in Prussia During the Late Nineteenth and Early Twentieth Centuries - Vögele, Jörg (Studia Historiae Oeconomicae, 2022)
In Germany, the recording of the causes of death has had a long tradition and goes back a long time in history, but remained unsystematic and nonuniform as it was an autonomous matter of the different German states. This article pursues the question of how the cause-of-death statistics developed in Prussia, the largest territorial state of the later German Reich. It is asked how these statistics, organized by the Prussian Statistical Bureau, have been related to the nationwide health policy since the 1870s. The historical development of official statistics in Prussia reveals that it is neither self-evident which information was collected, nor the criteria according to which this was done. Rather, the data actually recorded are the result of complicated negotiation processes between different actors, not only within the statistical offices, but also between the most diverse interest groups from science, politics and the state.